Isolation, characterization and antimicrobial activities of polyacetylene glycosides from Coreopsis tinctoria Nutt. (April 2017) - Guo, Jia; Wang, Ao; Yang, Ke; Ding, Hao; Hu, Yimin; Yang, Yumeng; Huang, Siqi; Xu, Jingguo; Liu, Tianxing; Yang, Haiyan; Xin, Zhihong
Abstract: Polyacetylene glycosides, (6Z, 12E)-tetradecadiene-8, 10-diyne-1-ol-3( R )-O- β -D-glucopyranoside (trivially named coreoside E) and (6Z, 12E)-tetradecadiene-8, 10-diyne-1-ol-3( R )-O- β -L-arabinopyranosyl-(1 → 2)- β -D-glucopyranoside (trivially named coreoside F), were isolated from buds of Coreopsis tinctoria Nutt., together with one known compound, coreoside B. Their chemical structures were elucidated by extensive spectroscopic analysis and on the basis of their chemical reactivities. Coreoside E exhibited high levels of antimicrobial activity against Staphylococcus aureus and Bacillus anthracis with minimum inhibitory concentrations of 27 ± 0.27 and 18 ± 0.40 μ M, respectively, whereas coreoside F and coreoside B showed weak antimicrobial activity against S. aureus and B. anthracis. Graphical abstract: Polyacetylene glycosides, with antimicrobial activity against Bacillus anthracis, were isolated from Coreopsis tinctoria Nutt. Their structures were elucidated by spectroscopic analysis and from their chemical reactivity. Highlights: Polyacetylene glycosides were isolated and identified from Coreopsis tinctoria Nutt. This is the first report concerning isolation of coreoside E and F from C. tinctoria . Coreoside E exhibited high levels of the antimicrobial activity.